Use of a robot in an imaginary space. Robot-assisted language learning with a friendship booklet (carnet d’amitié) - Peura, Liisa; Mutta, Maarit (Walter de Gruyter GmbH, 2026)
The integration of technology, including social robots, into classrooms has paved the way for new opportunities in second-language (L2) learning. This emphasises the importance of understanding child–robot interaction (CRI) and its impact on comprehensive language development. This study investigated CRI in a French L2 setting through young learners’ L2 written productions and visual expressions, adopting an embodied digital interaction perspective. It explored the intersection of pedagogy and technology in education, aligned with digital language practices and robot literacy. Over four months, young learners engaged with a social robot in French language learning, using a friendship booklet (carnet d’amitié) task to establish rapport and encourage free interaction. We observed a transition from scripted interactions to a dynamic “imaginary space” within the CRI and the extended interaction that positively influenced engagement and language exploration. The learners exhibited diverse language strategies to convey meaning, reflecting metalinguistic awareness and adaptability within the French language framework. This study provided insights into the integration of social robots in L2 education, highlighting the transformative potential of CRI and the imperative for critical robot literacy.